Common hierarchies, varied rules - the problem of governing community first responders in prehospital care for quality standards: documentary discourse analysis - Gupteswar Patel; Viet-Hai Phung; Ian Trueman; Roderick Orner; Aloysius Niroshan Siriwardena (BMC, 2023)
Abstract A key focus is placed on engaging communities to become involved in making decisions to support health and care services in healthcare policies in England, UK. An example is the deployment of volunteers such as community first responders (CFRs), who are members of the public with basic life support skills, trained to intervene in emergency situations prior to the arrival of ambulance services. CFR policies have been devised by National Health Service (NHS) Trusts as a way of governing these and related activities. This paper critically examines the discourse around CFR policies to understand how CFR roles are organised and monitoring governance mechanisms are delineated in ensuring quality care delivery. We collected ten CFR policies from six ambulance services. Inductive analysis, guided by Foucault's theory, enabled the identification of themes and subthemes. We found that Trusts have a common goal to make care quality assurances to regulatory bodies on CFR roles, and this is depicted in common hierarchies of individual responsibilities across Trusts. However, policies that govern approaches to CFRs activity vary. Firstly, the paper highlights institutional approaches to ensuring public safety through the application of organised surveillance systems to monitor CFR activities, and draws parallels between such surveillance and Foucault's docile bodies. Secondly, the paper discusses how varying rules in the surveillance system compromises safety by decentralising knowledge to regulatory bodies to whom NHS Trusts must make safety assurances. We suggest that stronger interrelationships between Trusts in considering the CFR role has potential to increase public safety and outline a clearer direction for CFRs.